PEMIDANAAN TERHADAP TINDAK PIDANA PENCABULAN YANG MEMILIKI HUBUNGAN KELUARGA BERDASARKAN PRINSIP PERLINDUNGAN ANAK (Studi Putusan No 533/Pid.Sus/2021/PN MGL) - Bryan Jupiter Chaniago; Azmi Syahputra (Faculty of Law, Universitas Trisakti, 2023)
Punishment for criminal acts of sexual immorality that have a family relationship based on the principle of child protection is the act of the perpetrator, namely the victim's uncle, who committed obscene acts against the victim's child, namely his biological nephew. The formulation of the problem is, what are the principles of child protection in criminal acts of sexual abuse that have family relationships and how to punish perpetrators of criminal acts of sexual abuse against children in family relationships. This research uses a descriptive type of normative research, with secondary data obtained by literature study. The analysis used is qualitative by drawing deductive conclusions. The results of the research, discussion and conclusions in this research are the principles of protection as victims of crime including, without discrimination, the best interests of the child, survival and development and respect for the review of convicted children in case Number 533/Pid.sus/2021/PN.MGL It is not appropriate considering that there was an error in the application of the article by the Public Prosecutor, which was not proportional because it involved the weighting of Article 13 paragraphs 1 and 2 of Law Number 17 of 2016.